Pendidikan Karakter Dalam Kitab Ayyuhal Walad Dan Relevansinya Dengan Pendidikan Karakter Di Indonesia - Syukri Kurniawan Nasution; Salminawati Salminawati; Zaini Dahlan (Kamaya: Jurnal Ilmu Agama, 2026)
The moral crisis among Indonesia’s young generation indicates that educational policies such as Strengthening Character Education (PPK) and the Independent Curriculum have not been fully effective in shaping students’ character. This condition underscores the urgency of reinforcing moral and spiritual values within the education system. This study aims to (1) describe the biography and educational thought of Imam Abu Hamid al-Ghazali, (2) analyze the concept of character education in Ayyuha al-Walad, and (3) examine its relevance to character education in Indonesia. Using a qualitative descriptive method with a library research approach and Krippendorff’s content analysis model, this study draws primary data from Ayyuha al-Walad and secondary data from al-Ghazali’s other works and supporting literature. The findings reveal that Ayyuha al-Walad encompasses key character values such as religiosity, honesty, perseverance, tolerance, independence, curiosity, appreciation of achievement, love of peace, responsibility, and social concern. These values are internalized through exemplary behavior, habituation, moral advice, and spiritual purification (tazkiyatun nafs). They align with Indonesia’s five pillars of national character education: religiosity, independence, mutual cooperation, integrity, and nationalism. Conceptually, al-Ghazali’s thought provides a philosophical and spiritual foundation for strengthening character education in Indonesia. The integration of moral and spiritual values into the curriculum can foster a generation that is intellectually capable, ethically grounded, and noble in character-consistent with the goals of national education.